Synthesis, characterization and influence of calcinations temperature on magnetic properties of Ni0.75Zn0.25Fe2O4 nanoparticles synthesized by sol-gel technique - Guan, B.H. (Science Publications, 2014)
The calcinations temperature is one of the important process parameter which influences the changes of magnetic properties in ferrites. This study provide better understanding of the influence of calcinations temperatures on the magnetic properties of Nickel Zinc ferrite consequently enable to tailor the magnetic properties of Nickel Zinc ferrite for specific application. Magnetic nanoparticles of Nickel Zinc ferritewere synthesized by sol-gel technique. Their crystallite size and the influence of calcinations temperature on magnetic properties were investigated by using X-Ray Diffraction (XRD) and Vibrating Sample Magnetometer (VSM). XRD results showed that the crystallization of the Nickel Zinc ferriteincreased as the calcination temperature increased. The results showed that single phase of Nickel Zinc ferritesamples can be obtained at various calcination temperatures from 800 to 1100Â°C. All Nickel Zinc ferritesamples exhibited ferrimagnetic behavior. VSM results showed that the saturation magnetization and coercivity values strongly influenced by the calcination temperature. Â© 2014 Science Publication.